Responses of crop production and soil health to chemical nitrogen fertilization in a maize-wheat rotation system - Deng, Meihua; Ma, Hua; Sadeghpour, Amir; Yang, Guiling; Hu, Yan; Yang, Dong (Frontiers in Environmental Science, 2023)
Chemical nitrogen (N) fertilizer is generally applied at high rates to maximize crop yields and also many non-grain farmlands are being converted into grain production to ensure grain production safety in China now. To test the effects of chemical N on crop production and soil health, a 3-year trial with urea and controlled-release fertilizer was conducted in a maize (Zea mays L.)-wheat (Triticum aestivum L.) system shifted from vegetable farmland by evaluating the effects of N fertilization on crop yields, typical soil properties, and soil bacterial community using 16S rRNA gene sequencing. The maximum crop yield and aboveground N uptake efficiency was achieved at 150 kg N ha-1 for wheat and 200 kg N ha-1 for maize. After three cropping seasons, the soil N properties were notably altered. For each kg of N applied, soil pH decreased at a rate of 0.0004–0.0012 pH units. The soil total N (TN) and total carbon (TC) content reached a higher stability at certain cumulative N application rates. However, the C/N ratio linearly decreased as N rate increased. Consequently, N application significantly decreased soil bacterial diversity owing to the decrease of α-diversity indexes of Shannon and Pielou_e. At the phylum level, chemical N application significantly depleted members of Acidobacteria, Chloroflexi and Nitrospirae, but the growth of Actinobacteria, Gemmatimonadetes, Firmicutes and Patescibacteria were improved. Compared with urea, the controlled-release fertilizer did not significantly change crop yields, soil bacterial diversity, soil TN and TC content. Overall, our results indicated that chemical N promoted crop yields at optimum application rates, but excessive N application could result in a decline in soil health, specifically accelerated soil acidification, a decrease in soil bacterial diversity, and soil C and N imbalance.